2019
DOI: 10.1016/j.jprot.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Platelet membrane lipid rafts protein composition varies following GPVI and CLEC-2 receptors activation

Abstract: Lipid rafts are membrane microdomains that have been proposed to play an important role in several platelet-signalling cascades, including those mediated by the receptors Glycoprotein VI (GPVI), and C-type lectin domain family 1 member B (CLEC-2), both involved in thrombus formation. We have performed a LC-MS/MS proteomic analysis of lipid rafts isolated from platelets activated through GPVI and CLEC-2 as well as from resting platelets. Our aim was to determine the magnitude of changes in lipid rafts protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Western blot was performed following an established protocol 41 in an independent cohort of concentrated secretome samples collected from three donors at days 3, 7 and 21, to validate the results obtained by the proteomic SWATH-based approach. Before immunoblotting, proteins were separated in 11% SDS-PAGE gels; 10 µg of protein was loaded per lane.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed following an established protocol 41 in an independent cohort of concentrated secretome samples collected from three donors at days 3, 7 and 21, to validate the results obtained by the proteomic SWATH-based approach. Before immunoblotting, proteins were separated in 11% SDS-PAGE gels; 10 µg of protein was loaded per lane.…”
Section: Methodsmentioning
confidence: 99%
“…Another study of the protein composition of membrane lipid rafts found large similarities after platelet stimulation via CLEC-2 or GPVI [67]. Intriguing is an observed loss of cytoskeletal proteins in the rafts from the activated platelets.…”
Section: Signalling C-type Lectin Receptor 2 (Clec-2)mentioning
confidence: 96%
“…Lipidomic mass spectrometry of complexed phosphoinositides and bound proteins showed that upon PI3K activation, many proteins can interact with 3-phosphorylated phosphoinositides through their PH domains, among which is the new adaptor protein DAPP1 [66]. Membrane lipid rafts of GPVI-stimulated platelets were also analysed in detail [67]. Oligophrenin as a small GTPase-binding protein regulator was furthermore recognised as a functional target of the GPVI-induced tyrosine kinase cascade [68].…”
Section: Collagen Receptor Glycoprotein VI (Gpvi)mentioning
confidence: 99%
“…Recently, the first proteomic comparative analysis of GEMs obtained from resting platelets and platelets activated through GPVI and CLEC-2 receptors was performed by Izquierdo et al [ 161 ]. The membrane fractions were isolated by sucrose gradient ultracentrifugation and GEMs-enriched fractions were determined by Western blot, then only the fractions enriched in flotillin-1 and lacking integrin αIIb were analyzed and GEMs proteins isolated.…”
Section: Detailed Review Of the Literature Of Proteomics Of Platelmentioning
confidence: 99%